5PSeq Explorer - Stevens, Irene (SciLifeLab Serve, 2026)
5PSeq is a method for profiling 5' phosphorylated mRNA undergoing decay. Degradation coincides with translation, as the enzymatic cleavage of the 5' end of mRNAs occurs right behind the last trailing ribosome. Therefore, information about ribosome dynamics can be obtained by profiling the degradome (5PSeq). 5PSeq Explorer is a web application that allows the visualisation of preprocessed co-translational degradation intermediates datasets in bacteria, Saccharomyces and Candida albicans in response to various stresses and drug treatments. Information about frame usage, translation start and termination sites, amino acid and codon usage is available.